(untitled) (Palimpsesto, 2017)
This paper describes the scientific career developed by Matus between 1906 and 1915. Particularly, attention is paid to the collection and organization of his anthropometrical and anthropological data, to his methodological discussions on techniques and instruments used, and to the academic and institutional networks he built throughout. In a context where defining a "Chilean race" was a prominent scientific and political objective, both studies allowed Matus to establish a scientific definition over the racial characteristics of the Chilean population.